A Study Of Psychophysical Factor (Heart Rate) For Driver Fatigue Using Regression Model - Ani, Mohammad Firdaus; Kamat, Seri Rahayu; M., Mohamad; Hambali, Ruzy Haryati; Husain, Kalthom (MJPHM, 2017)
Driving activity has become more important as this medium being practical, cheaper, and faster in connecting human from one to another place. However, in some occurrence, it can cause accidents as they get fatigued while driving. Driver fatigue is one of the top contributors to the road accidents and can be dangerous as other road safety issues such as drink driving and there are no laws regulating driver fatigue. Therefore, the main purpose of this study is to develop the regression modeling of a psychophysical factor for drivers’ fatigue which can predict the relationship between the process input parameters and output responses. The study was participated by ten subjects. The heart rate was taken and recorded using heart rate monitor. This study is expected to formulate and develop the regression modeling of the psychophysical factor by using regression analysis. Design Expert 8.0.6 software was used for the regression analysis. The regression model was successfully developed and validated. The modeling validation runs were falls within the 90% prediction interval of the developed model and the residual errors were less than 10%. The study also discovered that the R2 value, 0.9400 which near to value of 1 means the linear regression line passes exactly through all points. The significant parameters that influenced the heart rate were also identified. Heart rate was influenced by the time exposure, type of road, and gender. Thus, the author believes there is a new contribution to the body of knowledge from this study.